Implicações De Programas De Iniciação À Docência Na Formação Inicial De Pedagogos - Roncon, Camila Leite Araujo [UNIFESP] (2018)
This Work Sought To Understand The Implications Of Two Initiation Programs For Teaching, The Institutional Program Of Initiatives For Teaching And The Pedagogical Residency Program, A Proposal For A Course In Pedagogy Of The Federal University Of São Paulo, In The Insertion Of Teachers . It Is Understood Here That The First Years Of Professional Practice Are A Striking And Fundamental Step In The Life Of The Teacher, Because It Is The Moment Of Transition From Student To Work As A Teacher. According To The Literature Of Reference Of This Area, This Stage Is Characterized By Tensions And Conflicts That Can Result In Sadness, Solitude And Even Abandonment Of The Profession. (Marcelo Garcia, 1999; Mizukami Et Al., 2002; Nóvoa, 1992). In This Way, This Work Started From The Hypothesis That Students Who Participate In Professional Insertion Programs Have A Formation That Is Closer To Reality, Inhibiting Or Ignoring The Presented Characteristics. Thus, The Egresses Of Both Programs Were Selected And Mapped To Those